The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1002/j.1537-2197.1967.tb06889.x
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Formation of Polyploidy and Its Effect in the Genus Musa

Abstract: Polyploidy was induced in two Musa species and their hybrid by means of immersing newly germinated diploid seedlings in 0.5% aq. colchicine solution. Tetraploid M. balbisiana plants were taller and more robust but had slower growth rate, droopier leaves, fewer suckers, and scantier root systems than the diploids. Tetraploidy affected fruit size and shape in M. balbisiana and in M. acuminata. Tetraploidy did not affect bunch size (the number of fruit‐bearing nodes) in M. acuminata banksii but caused great reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Alternative breeding strategies based on colchicine-induced autotetraploids have been proposed as a means of introducing disease resistance into breeding programs (Vakili 1967;Stover and Buddenhagen 1986). By using improved, disease-resistant diploid bananas, and inducing autotetraploids from these, !greater genetic diversity can be introduced into a breeding population.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative breeding strategies based on colchicine-induced autotetraploids have been proposed as a means of introducing disease resistance into breeding programs (Vakili 1967;Stover and Buddenhagen 1986). By using improved, disease-resistant diploid bananas, and inducing autotetraploids from these, !greater genetic diversity can be introduced into a breeding population.…”
Section: Introductionmentioning
confidence: 99%
“…Ortiz & Vuylsteke (1992) reported that locus P1 segregated in trisomic ratios in plantain-derived diploid test-crosses derived by crossing triploid 'French' plantains and 'Calcutta 4'. Simmonds (1976), based on Vakili (1967), explained that fruits of triploid Musa cultivars grow faster and larger than diploids. Indeed, in natural banana germplasm, triploids have heavy bunches of big fruits whereas diploids have bunches with small fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Assim sendo, para cada espécie e tipo de material a ser tratado, a concentração do alcalóide deve ser determinada (VAKILI, 1969 Tabela 1. Valores médios da taxa de sobrevivência, porcentagem de plântulas com múltiplas brotações, primeira medição de altura de parte aérea das plântulas (três meses após tratamento com colchicina) (cm) e segunda medição de altura de parte aérea das plântulas (sete meses após tratamento com colchicina) (cm) de Cattleya tigrina, tratadas com diferentes concentrações de colchicina (g.L -1 ) e diferentes intervalos de tempo (horas).…”
unclassified